Linear regression analysis - Seber, G. A. F.; Lee, Alan J. (Wiley series in probability and statistics, 2003)
Requiring no specialized knowledge beyond a good grasp of matrix algebra and some acquaintance with straight line regression and simple analysis of variance models, this work covers the diagnostics and methods of model fitting.